Lichen diversity in the Edough Peninsula, North East of Algeria - Ahmed Monia, Ali; Rafika, Brakni; Tarek, Hamel (Botanica Complutensis, 2018)
This study was carried out with the aim of enriching the list of lichens of Algeria, for this reason we have prospected 2 stations “Les Cascades des Vautours” and “Dar smayer” at 442 and 856 m of altitude, Edough Peninsula on the North East Algerian coast. The annual precipitation is relatively abundant, of the order of 1000 mm. Seventythree taxa were registered belonging to 15 families of which 8 taxa: Cladonia cervicornis subsp. verticillata (Hoffm.) Ahti, C. ramulosa (With.) J.R. Laundon, C. humilis (With.) J.R. Laundon, Nephroma parile (Ach.) Ach., Parmelinopsis afrorevoluta (Krog & Swinscow) Elix & Hale, Ramalina siliquosa (Huds.) A.L. Sm., Usnea esperantiana P. Clerc and Xanthoparmelia conspersa (Ehrh. ex Ach.) Hale, which were never mentioned in Algerian lichen flora. Se ha realizado este estudio con el objetivo de enriquecer la lista de líquenes de Argelia donde se han prospectado 2 estaciones “Les Cascades de Vautours” y “Dar smayer” situadas a 442 y 856 m de altitud respectivamente de la Península de Edough en el NE de Argelia. La precipitación anual es abundante y cercana a los 1000 mm. Se han encontrado 73 taxones pertenecientes a 15 familias diferentes, con 8 taxones: Cladonia cervicornis subsp. Verticillata (Hoffm.) Ahti, C. ramulosa (With.) J.R. Laundon, C. humilis (With.) J.R. Laundon, Nephroma parile (Ach.) Ach., Parmelinopsis afrorevoluta (Krog & Swinscow) Elix & Hale, Ramalina siliquosa (Huds.) A.L. Sm., Usnea esperantiana P. Clerc y Xanthoparmelia conspersa (Ehrh. ex Ach.) Hale, que constituyen novedad para la flora liquénica argelina.